Analisis Efektivitas Bauran Pemasaran dalam Perspektif Islam pada Penerbitan Media Pro-U Yogykarta - Mu'tashim Billah Murtadlo (At-Tauzi : Jurnal Ekonomi Islam, 2016)
This research aims to determine the concept of marketing mix applied by Pro-U Media Publishing from Islamic perspective and to analyze the effectiveness of its marketing mix in achieving their target revenue of the company each and every month. The research method used is descriptive qualitative with target approach. Data sources in this research are primary data obtained from the facts that exist in Pro-U Media Publishing, and secondary data collected from books, journals, and other supporting literatures. Data collection technique used in this study is by observations, interviews, and documentation. Non-statistical analysis technique used in this research is interactive analysis. Research results show that the implementation of marketing mix in Pro-U Media Publishing is in accordance with Islamic perspective. In addition, research results show that productis the most effective variable, among the other three variables (price, place, and promotion) in the implementation of marketing mix of Pro-U Media Publishing, in increasing the average target revenue of the company as a whole.